(untitled) (International Journal of Physiotherapy, 2020)
Background: The need for intense rehabilitation protocols with easy applicability to improve for patient adherence and harness the potential neuroplasticity leading to improvement in the quality of life (QOL) in post-stroke patients. Several studies have described the benefits of virtual reality and video games in rehabilitation. Aims: To explore and determine if Computer game-based rehabilitation for post-stroke upper limb deficits after stroke is superior to conventional therapy in terms of (1) ICIDH based outcomes (2) Intervention duration (3) acceptability and adherence to the intervention. Methods: This systematic review and meta-analysis followed PRISMA guidelines. Several electronic databases were searched using specific keywords, to measure the effects of computer-game-based therapy in post-stroke patients compared to conventional therapy. Results: 14 studies were included after a systematic review, out of which 11 were included for analysis. Studies recording Wolf motor function test and box and block test have shown improvements with Computer-game-based therapy in addition to conventional therapy. No improvements were recorded in impairments and patient participation/Quality of life. CGBT was acceptable and reported no adverse effects. Conclusions: Computer-game-based therapy or non-immersive virtual rehabilitation is effective and acceptable for upper limb rehabilitation after stroke. With significant improvement in ‘activity-limitation,’ this mode of rehabilitation can be adapted for patient-specific needs. Its effects on impairment and quality of life need further exploration.